The Effect of Interpretation Context In Community Communication - arief, abid fathurrahman; Muta’ali, Abdul (Journal Of Middle East and Islamic Studies, 2023)
Today’s, general of Muslim community only recognizes one type of recitation method of the Qur'an, specifically riwayat Hafsh 'an Ashim min Tariq Syathibiyah. This recitation became an international standard among qiraat scholars, students, and the general of Muslims. Qiraat sciences collect the principles of different recitation of the Qur'an which are attributed to qiraat scholars (a'immah al-qira'at). Based from Abul Fadhl Ar-Razi's theory about the meaning of Sab'atu Ahruf, the different recitations of the Qur'an (Ikhtilaf al-Qira'ah) have several criteria, including: Differences in nouns (Isim), verbs (Fi'il), cases ( I'rab), adding and subtracting words (Ziyadah wa Naqishah), prioritizing and ending a pronunciation (Taqdim wa Ta'khir), changing letters (Tabdil) and dialect differences (lahjah). This difference of recitations has connection with Arabic morphology (Sharaf), for example in the words "tabayyanu" and "tatsabbatu" in Surah An-Nisa verse 94 and Al-Hujurat verse 6. The purpose of this study is to find out the exact contextual meaning of the differences in qiraat so that it can be applied in the life. The research method used is descriptive-analytic method with literature review and observation. Based on the study that I described in this article, it can be concluded that the differences in the qiraat of the sentences 'Tabayyanu' and 'Tatsabbatu' have different contexts of meaning and complement each other in relation to communication ethics.